UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF TIPE TALKING STICK TEMA 9 SUBTEMA 1 PADA KELAS V - Yusroh Yusroh (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
The problem of this research is low students’ scores of learning outcomes in themes 9 things around us, sub themes 1 single object and mix objects proved by accomplished their midterm test that over the minimum criteria of mastery, total 11 students and 15 students who do not complete to the minimum criteria of mastery. The goal of this research is to fix the students’ low learning outcomes by applying a talking stick model. Kind of the research is classroom action research. The subjects of this research were all students of class V that had 26 students, consisting of 9 boys and 17 girls. This research had four stages, they were planning, implementation, observation and reflection. In this research, researchers did 2 cycles. Each cycle had three meetings. Collecting the data using a teacher observation sheet, student worksheet, student overcomes test, and documentation. The result of the research shows that the teacher’s activities in the first cycle are is categorized as good, the second meeting is good, and the third meeting is good. Students’ activities at the first cycle on the first meeting are categorized is good enough, the second meeting as good, and the third meeting is good. In the second cycle, the the first meeting is categorized as good, the second meeting is good, and the third meeting is good. Students’ problems in first cycle reached 58% and the second cycle reached 85%. Based on the result of this research, it can be assumed that learning through a talking stick model on learning themes 1 single object and mixed objects can increase students’ learning outcomes.